16 & Pregnant' stars to speak on campus, March 2 - Fresno State::::::::: (2013)
16 & Pregnant' and 'Teen Mom' reality show stars known as 'the couple who chose adoption,' will speak about their open adoption, adoption in today's society and other important challenges teens and young adults are facing today.